Preservasi Naskah Kuno Koleksi Masjid Agung Surakarta - Riswinarno Riswinarno (Panangkaran: Jurnal Penelitian Agama dan Masyarakat, 2017)
This article discusses the preservation of ancient scripts in the Surakarta Grand Mosque collection. A majority of texts are former books that were used as teaching materials at the Manba’ul ‘UlumMadrasah in Surakarta. A madrasah established by the Kasunanan sultanate of Surakarta during the reign of Sri SusuhunanPakubuwono IX (1861-1893). The presence of these texts serves as evidence in the intensity of the sultanate in developing Islam through the education process, hence making them a highly significant source of written history.There are currently 93 scripts in existence, however the conditions require serious preservation efforts. Aside from natural degradation by time, other ecological factors that should be considered in their preservation are quite lacking. Each script has differing conditions, thus the need for special treatment. For that reason, preservation efforts must be undertaken immediately.